Computer Use In Esl Classrooms In Area Of Conflict: Teachers’ Selfefficacy And Barriers Towards Computer Use In The Palestinian Public Schools - Tamimi, Nasser Deeb Husni (2018)
This study was designed to investigate factors related to computer use for instructional purposes. The aim was to examine level of computer use in Palestinian public schools, English teachers’ computer self-efficacy with respect to computer use in teaching, the barriers such teachers face when using computers in their teaching and the relationships between teachers' computer self-efficacy and their usage of computers in teaching. The study derived its theoretical framework from Technology of acceptance model 3 (TAM 3) which is proposed by (Venkatesh & Bala, 2008). The sample of this study consisted of 186 English teachers from Palestinian public schools. In addition, to six English teachers were selected for a semi structured interview. Validity and reliability were established for the survey instrument. Descriptive analysis and inferential statistical techniques were used as well. Findings in this study revealed that level of computer use for instructional purposes is relatively low. Findings indicated that level of computer use is high in preparation areas such preparing quizzes and preparing tests while it is relatively low in other levels such as in areas for delivery of teaching, evaluation of teaching and communication purposes. Findings of the study also showed that English teachers have got positive self-efficacy towards computer use. They possess positive attitudes towards the effectiveness of computer use for instructional purposes but findings indicated that these teachers may be not prepared yet to use computers in their teaching due to many barriers.